Lines on Stone : The Prehistoric Rock Art of India. Revised and Enlarged Edition including 2500 Illustrations from the Clayman Archive - Neumayer, Erwin (Brill | Manohar Publishers & Distributors, 2016)
Lines on Stone and the accompanying CD-Rom of the dayman Archive offer an encyclopaedic view of the pre- and protohistoric Rock Art of India. The 3,000 or so illustrations give a sweeping view of the aesthetic as well as thematic vastness of the earliest Indian art. We see people in their daily chores, women nursing babies, carrying baskets, catching rats, working grinders, emptying baskets, while men with their microlith tipped spears hunt animals, climb trees, shoot their arrows at birds or fish. But we also see many enigmatic sceneries, which we can not 'read' any more, but then we know that the people of long past must have had their own mythologies which we might not be able to disentangle any more. These rock pictures therefore are a treasure which has to be cherished and protected like the proverbial apple of the eye: it is our only possibility to look into our own past, a past of which we have little otherwise. Although rock pictures were noticed by antiquarians in the nineteenth century, the systematic study of these pictures started only after the discovery of Bhimbetka and the excavations which followed during the 1970s. Bhimbetka is by now a well known rock art site, a tourist site of the first order in Central India on which the prestigious UN world heritage status of cultural property of mankind was conferred. But it also should be remembered that many more such sites are threatened by the economic transformation of India.